Integrasi Platform Digital dalam Pengembangan Kuliner Lokal untuk Mendukung Gastronomy Tourism Berkelanjutan - Rahmat Kusnedi; Muhammad Wildan; Muhammad Irfan; Dikki Z Choesrani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Food tourism is increasingly recognized as a strategic component in enhancing the competitiveness of tourism destinations, particularly thru the development of local cuisine based on local wisdom. However, most research still views digital platforms as partial promotional tools and has not yet studied how to use them systematically to build a sustainable culinary tourism ecosystem. The purpose of this study is to examine how digital platforms contribute to the development of local cuisine and how they contribute to the strengthening of sustainable culinary tourism. This is the culinary tourism destination that is the subject of this study, which was conducted using the case study method. Data was collected thru in-depth interviews with culinary MSME producers, destination managers, and tourists, as well as online observations via social media, travel review platforms, and culinary markets. The research results show that the value of tourism experiences can be enhanced, destination identity strengthened, and active participation of local SMEs increased thru the integration of digital platforms that connect visual promotion, tourist interaction, and digital culinary stories. The latest finding in this research is the development of a multi-platform digital integration model that serves not only as a marketing tool but also as a collaborative ecosystem that helps local economic growth, preserves culinary cultural heritage, and enhances the competitiveness of tourist destinations. The results of this research contribute conceptually and practically to building sustainable digital-based culinary tourism strategies.